VASH-1 Regulates Oxidative Stress and Fibrosis in Diabetic Kidney Disease via SIRT1/HIF1α and TGFβ1/Smad3 Signaling Pathways - Ren, Huiwen; Shao, Ying; Wu, Can; Lv, Chuan; Zhou, Yang; Wang, Qiuyue (Frontiers in Molecular Biosciences, 2020)
Aims: To investigate the role of Vasohibin-1 (VASH-1), silence information adjustment factor 2-related enzyme 1 (SIRT1)/hypoxic-inducible factor 1α (HIF1α) and transforming growth factor-β1 (TGFβ1) /Smad3 signaling pathways in oxidative stress and fibrosis of diabetic kidney disease (DKD). Materials and methods: A diabetic rat model was established in vivo and rat mesangial cells (RMCs) were cultured in vitro with high glucose via transfection with Vash1 small interfering RNA (siRNA), Hif1a siRNA, Sirt1 siRNA and TGFβ1/ Smad3 pathway inhibitor (SB431542). Renal histology was used to detect renal changes. Real-time PCR and western blot were used to analyze the expression of VASH-1, SIRT1, HIF1α, TGFβ1, Smad3, vascular endothelial growth factor (VEGF), connective tissue growth factor (CTGF) and fibronectin (FN). Expression levels of tumor necrosis factor-α (TNFα), TGFβ1, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX) and malondialdehyde (MDA) in rat tissues and cell culture supernatant were detected by ELISA and chemiluminescence assay, while cell proliferation was detected by CCK-8. Results: The level of VASH-1 in renal tissues of diabetic rats was decreased, while both high glucose and Vash1 siRNA inhibited the expression of VASH-1 and SIRT1, increased the levels of HIF1α, TGFβ1 and Smad3 in RMCs, thus up-regulating oxidative stress and fibrosis factors, and abnormally increasing cell proliferation activity (P<0.05). However, inhibition of SIRT1/HIF1α signaling pathway only reduced TGFβ1 and Smad3 (P<0.05), while VASH-1 remained unchanged (P>0.05). Conclusion: VASH-1 was under-expressed in renal tissues of diabetic rats and regulated the pathological process of oxidative stress and fibrosis in DKD via downstream SIRT1/HIF1α and TGFβ1/Smad3 signaling pathways.